Covid-19 has turned home advantage into home disadvantage in the German soccer Bundesliga - Tilp, M.; Thaller, S. (Frontiers in Psychology, 2020)
The main factors for home advantage (HA), quantified by the number of points won at home expressed as a percentage of all points, are believed to be crowd support, territoriality, familiarity, and travel fatigue. In 2020, the German Soccer Bundesliga interrupted its championship due to the Covid-19 pandemic after 25 rounds and the last nine rounds were played without audience. This unique situation allowed studying the effect of spectators on the team's performance and the referee's decisions. We hypothesized a decrease in HA and a more balanced distribution of fouls and disciplinary cards in the games without audience (GWOA) compared to the games with audience (GWA). We evaluated n = 223 GWA and n = 83 GWOA of the season 2019/20 and all games of the preceding season 2018/19 to analyze the distribution of game outcomes (wins, losses, and draws) and HA. We analyzed the number of fouls, disciplinary cards, and penalty kicks. We found significant differences in HA between GWA (HA = 54.35%) and GWOA (HA = 44.1%) as well as GWOA and games of 2018/19 (HA = 57.63%). The distribution of game outcomes in GWOA did not differ from GWA but differed significantly from 2018/19 (p = 0.031). The distribution of fouls showed a significant difference to equal distribution in GWA [home: 2,595 (48.56%); away: 2,749 (51.44%)] but not in GWOA [home: 1,067 (50.54%); away: 1,044 (49.46%)]. In the GWOA, we counted 178 (51.1%, home) and 170 (48.9%, away) cards, representing a significant difference in the distribution to GWA [home: 405 (44.85%); away: 498 (55.15%)]. The number of red cards differed significantly from an equal distribution for GWA (14 home and 28 away) but not for GWOA (eight home and seven away). In the last nine rounds without audience, we observed more home losses (36) than home wins (27). Hence, the Covid-19 lock-down led to a home disadvantage. One reason for this surprising result could be that the home team is missing an important familiar aspect when playing in their empty stadium without social support from their home audience. Furthermore, both teams know about the HA thus the away team could be more motivated in this unusual situation.